Programa de operaciones aritméticas con base en la yupana en el cálculo aritmético en estudiantes del primero de secundaria del Callao - Mejía Quispe, Justo Javier (2011)
This research is experimental and uses a pre-experimental design of a single group is to determine to what extent Arithmetic Program based on the performance increase yupanas Computation in the seventh grade students an Educational Institution of Callao. It has been used as a purposive sample, 13 men and 15 women, average age 12 years. We designed and implemented the pre-test and post-test, these being validated by experts. In addition, the pilot had a level of reliability of 0.867 and 0.853 respectively. The results show a significant improvement (p <0.05) in the experimental group in the dimensions of addition, subtraction, multiplication, division.